Efektivitas Les Literasi dalam Meningkatkan Kemampuan Membaca Siswa SDN 2 Ampenan - Qalby, Nurul; Astawa, I Made Suwasa; Khaer, Fikratul (Mataram University, 2025)
This study aimed to examine the effectiveness of a reading literacy tutoring program in improving students’ reading skills at SDN 2 Ampenan. The subjects of the study consisted of 16 students, including 7 third-grade students, 5 fourth-grade students, and 4 fifth-grade students. The research employed Classroom Action Research (CAR) conducted in two cycles, with stages of planning, implementation, observation, and reflection. Research instruments included student activity observation sheets and reading skill tests covering five aspects: accurate word recognition, pronunciation accuracy, word completeness, reading fluency and proper intonation, and text comprehension. The results indicated a significant improvement in students’ reading skills, with the average score increasing from 56.4% in the pre-action stage to 85.2% in Cycle II, with the largest improvement observed in text comprehension (60%). Student activity also increased from 58.4% in the pre-action stage to 88.0% in Cycle II, moving from the “Adequate” to “Very Good” category. These findings align with previous studies in Indonesia, which emphasize that structured literacy instruction combined with intensive guidance can enhance students’ reading skills and learning motivation. Thus, reading literacy tutoring can be recommended as an effective instructional strategy to improve literacy in elementary schools.